The Role Of Motivation In Mediating The Influence Of Organizational Culture On Employee Performance - Ryan Hadi Saputra; I Gusti Made Suwandana (PT Publikasiku Academic Solution, 2024)
In a business, human resources are crucial. High-quality human resources may provide value to a business, boost its competitive edge, and aid in decision-making that will ultimately improve worker performance. Without effective staff performance, the company cannot accomplish its objectives. In Denpasar City, Bali, this study was carried out at one of the state-owned businesses. The pre-survey's findings suggested that there could be issues with staff performance at the research location. 41 employees were chosen as the study's sample using the saturation sampling approach. Questionnaires were distributed and interviews were conducted in order to collect data. Path analysis with SPSS, the Sobel test, and the VAF test were the data analytic methods employed in this study. Based on the study's findings, it can be concluded that organizational culture has a positive and significant impact on worker performance, motivation has a positive and significant impact on worker performance, and motivation can mediate the effect of organizational culture on worker performance. From the standpoint of self-determination theory, the implications of this study conceptually validate the findings of earlier research. The research's practical implications offer a guide for policy that managers and staff may use to enhance employee performance through organizational culture and motivation.